Mapping and Visualization of Plagiarism Research - Singh, M. P.; Kumar Bharati, Vijay (Journal of Information and Knowledge, 2020)
The paper seeks to map and visualize the published research on Plagiarism indexed by Scopus database during 2010-2019. A total of 1882 articles were retrieved using keyword search TITLE: (plagiarism). Microsoft Excel is used for graphical representation of the data for document type and funding agencies, etc. and the VOS viewer science mapping framework (Van Eck & Waltman, 2010) is used for analyzing the research trends and collaboration among scientists, organizations, and countries. Research on Plagiarism is growing. The USA is the biggest collaborative country that has a larger number of scholarly publications followed by United Kingdom, India, China, Thailand, Spain, and Australia.